Mechanical Characteristics of 6063 Aluminum-Steel Dust Composite. (8th August 2012) - Adeosun, S. O.; Akpan, E. I.; Sekunowo, O. I.; Ayoola, W. A.; Balogun, S. A.
Abstract : Studies on the effect of steel dust (EAF dust) addition on the mechanical properties of 6063 Aluminium alloy have been carried out. The cast composite samples contain steel dust from 2–20 wt% produced in sand mould. These cast samples were homogenized, cold rolled, and solution-treated. The solution treated samples were normalized in still air, some quenched in water while some were tempered after quenching. Tensile and hardness responses were determined in all these processed samples. The results obtained reveal that 10 wt% steel dust in aluminium 6063 improved the ultimate tensile strength to 111.09 MPa and a corresponding hardness of 51.2 HV. Microstructural analysis shows iron containing intermetallics which are well distributed in the matrix with its morphology depending on the heat treatment and deformation imposed on them. Tensile strength and hardness of the composites was also found to depend on the volume fraction of intermetallics in the matrix.